A Molecularly Imprinted Polymer Nanobodies (nanoMIPs)-Based Electrochemical Sensor for the Detection of Staphylococcus epidermidis - Witsanu Rapichai; Chularat Hlaoperm; Adriana Feldner; Julia Völkle; Kiattawee Choowongkomon; Jatuporn Rattanasrisomporn; Peter A. Lieberzeit (Sensors)
Methicillin-resistant Staphylococcus epidermidis (MRSE) contamination is commonly found on human skin and medical devices. Herein, we present a sensor utilizing molecularly imprinted polymer nanobodies (nanoMIP) for recognition and electrochemical impedance spectroscopy (EIS) to detect S. epidermidis. Sensor manufacturing involves synthesizing nanoMIP via solid-phase synthesis using whole bacteria as templates. Screen-printed gold electrode (AuSPE)-modified 16-mercaptohexadecanoic acid (MHDA) served to immobilize the nanoMIPs on the sensor surface through an amide bond, with the remaining functional groups blocked by ethanolamine (ETA). Scanning electron microscope (SEM) analysis of the modified AuSPE surface reveals immobilized spherical nanoMIP particles of 114–120 nm diameter, while atomic force microscope (AFM) analysis showed increased roughness and height compared to bare AuSPE. The sensor is selective for S. epidermidis, with a remarkable detection limit of 1 CFU/mL. This research demonstrates that the developed nanoMIP-based sensor effectively detects S. epidermidis. Further research will focus on developing protocols to integrate the nanoMIP-based EIS sensor into medical and industrial applications, ultimately contributing to improved safety for both humans and animals in the future.